Caribbean Report 26-04-1995 - Rowe, Yvette (anchor); Richards, Ken (correspondent); Alleyne, Brian (interviewee); James, Edison (interviewee); Ninvalle, Pete (correspondent); Bousquet, Rufus (interviewee); Amiot, Michel (interviewee); Niles, Bertram (correspondent); Alleyne, Gary (correspondent) (The British Broadcasting Corporation, 1995)
Fears of possible election violence in Dominica after a number of incidents at political rallies. Dominica Freedom Party Leader Brian Alleyne and Opposition Leader Edison James comment on these incidents. St. Lucia's Financial Services Minister, Rufus Bousquet states he has nothing to do with the alleged misappropriation of UN funds. The United Nations International Drug Control Programme (UNDCP) has terminated a drug abuse project in St. Lucia. Michel Amiot, Director of the Caribbean Regional Office at UNDCP, spoke about the delays in implementation and lack of political will. In Barbados, Prime Minister Owen Arthur devoted a portion of the budget to Barbados relations with CARICOM. The Jamaican government has given a further indication of its continued commitment to CARICOM in its recent budget. The government is attempting to achieve freely convertible currencies across the Caribbean Basin. In the US, the Clinton Administration hopes to persuade Republican law-makers to weaken key aspects of a legislative proposal.
1. Headlines with Yvette Rowe (00:00-00:28)
2. Fears of possible election violence in Dominica after a number of incidents at political rallies (00:29-02:53)
3. St. Lucia's Financial Services Minister states he has nothing to do with the missing UN funds (02:54-07:32)
4. A United Nations agency has terminated a drug abuse project in St. Lucia (07:33-11:08)
Keywords: Political violence -- Dominica; Dominica -- Politics and government; Political campaigns -- Dominica; Political corruption -- Saint Lucia; Government accountability -- Saint Lucia; Saint Lucia -- Politics and government; Drug abuse -- Prevention -- Finance; Barbados -- Politics and government; Budget -- Barbados; Barbados -- Economic policy; Free trade -- Caribbean Area; Caribbean Area -- Economic integration; Currency convertibility -- Caribbean Area; Monetary policy -- Jamaica; Anti-Americanism -- Cuba; Cuba -- Foreign relations -- United States; United States -- Foreign relations -- Cuba; Cuban Americans; United Nations -- Finance; Caribbean Community